Evaluasi Manajemen Risiko Keamanan Siber pada Infrastruktur Digital Pemerintah: Studi Kasus Pusat Data Nasional (PDN) - Syarifa Tommy; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The data leak incident that hit the National Data Center (NDC) in June 2024 became one of the biggest cyber crises in the history of the Indonesian government's digital transformation. The attack, which used LockBit 3.0 ransomware, paralyzed hundreds of public services, showing the weakness of the national cybersecurity system and decreasing public trust in the government. This research aims to analyze the chronology, impact, and mitigation strategies that can be applied in overcoming the digital security crisis in the government sector. Using a case study-based qualitative-descriptive study approach, data was collected from documentation, official government reports, scientific journals, and media coverage. The results show that the main causes of data leakage lie in weak security management, absence of data backup, and poor implementation of digital system governance. The study recommends the need for national policy updates, human resource capacity building, and the adoption of cutting-edge security technologies to strengthen government cyber resilience.